2019
DOI: 10.1155/2019/3639693
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Lever Sign Test in Acute, Chronic, and Postreconstructive ACL Injuries

Abstract: Background. The aim of this study is to determine the diagnostic accuracy of lever sign test in acute, chronic, and postreconstructive ACL injuries. Methods. In total, 78 patients (69 male, 9 female) were subjected to clinical instability tests including Lachman, anterior drawer, pivot shift, and lever sign when an injury of the ACL was suspected. All tests were performed bilaterally in all patients in acute, chronic period and patients who underwent surgery after the anaesthesia and after the reconstruction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 22 publications
(32 reference statements)
0
23
0
9
Order By: Relevance
“…The anterior drawer test has a sensitivity of 56% and a specificity of 82% and is a sign of ACL rupture. It is more sensitive for fibres in the anteromedial beam[ 99 , 100 ]. There is a variety of the anterior drawer test that is externally rotated and specifically allows assessment of posterior-internal structures[ 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anterior drawer test has a sensitivity of 56% and a specificity of 82% and is a sign of ACL rupture. It is more sensitive for fibres in the anteromedial beam[ 99 , 100 ]. There is a variety of the anterior drawer test that is externally rotated and specifically allows assessment of posterior-internal structures[ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lachman test: This is the main test to be carried out on an acute injury[ 100 ]. It is performed with the knee in a 30° knee flexion position and a force is applied in an anterior direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the original data omitted (400 tests with no false positive or false negative results), the LR + decreased from 128.0 to 13.1 indicating verification and case–control bias [ 59 ]. Other studies reporting on the Lever sign test are also at risk of verification bias [ 9 , 18 , 26 , 33 , 39 , 43 , 49 , 72 ]; therefore, results based on time since injury and tear type should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Gürpınar et al [25] reported a sensitivity value of 80.6% for Lachman, 77.4% for the Anterior Drawer, 51.6% for the pivot, and 91.9 for the lever test in the acute phase. For the chronic phase, these values were reported as 83.9%, 79.0%, 56.5% and 91.9%, respectively.…”
Section: Quadricepsmentioning
confidence: 99%